Family history of cancer and the risk of bladder cancer: A case–control study from Italy. (June 2017) - Turati, Federica; Bosetti, Cristina; Polesel, Jerry; Serraino, Diego; Montella, Maurizio; Libra, Massimo; Facchini, Gaetano; Ferraroni, Monica; Tavani, Alessandra; La Vecchia, Carlo; Negri, Eva
Highlights: A hospital-based case-control study, enrolling 690 cases and 665 controls. The association between family history of cancer and bladder cancer was evaluated. Family history of bladder cancer was associated to 2-fold increased bladder cancer risk. The risk was greater when that relative was younger at diagnosis. Family history of hemolymphopoietic cancers increased bladder cancer risk. Abstract: Background: A family history of bladder cancer has been associated with the risk of bladder cancer, but quantification of the excess risk in different populations is still a relevant issue. Further, the role of a family history of other cancers on the risk of bladder cancer remains unclear. Methods: We analyzed data from an Italian case–control study, including 690 bladder cancer cases and 665 hospital controls. Odds ratios (ORs) were estimated through unconditional logistic regression models, adjusted for sex, age, study center, year of interview and further for education, smoking and sibling's number. Results: The OR for family history of bladder cancer was 2.13 (95% confidence intervals (95%CIs) 1.02–4.49) from the model with partial adjustment, and 1.99 (95%CI 0.91–4.32) after additional adjustment for smoking and siblings' number, based on 23 cases (3.3%) and 11 controls (1.7%) with a family history of bladder cancer. The fully adjusted OR was 3.77 when the relative was diagnosed at age below 65 years. Smokers with a family history of bladder cancer had a four-fold increased risk compared to non-smokers without a family history. Bladder cancer risk was significantly increased among subjects with a family history of hemolymphopoietic cancers (OR = 2.97, 95%CI 1.35–6.55). Family history of cancer at other sites showed no significant association with bladder cancer risk. Conclusion: This study confirms an approximately two-fold increased risk of bladder cancer for family history of bladder cancer, and indicates a possible familial clustering of bladder cancer with cancers of the hemolymphopoietic system.